ショウワ キチ エンガン テイチャク ヒョウイキ ニ オケル アイスアルジー オヨビ ショクブツ プランクトン ノ キソ セイサン リョウ ノ ミツモリ - 佐藤, 博雄; サトウ, ヒロオ; 渡辺, 研太郎; ワタナベ, ケンタロウ; 星合, 孝男; ホシアイ, タカオ; Satoh, Hiroo; Watanabe, Kentaro; Hoshiai, Takao (1991)
P(論文) 昭和基地周辺定着氷域において, 1983年2月から翌年の1月にかけて水深12mの北の瀬戸で基礎生産量を試算した。計算には昭和基地で測定された天空日射量, 日長時間, 現場での積雪量, 氷厚および海水による光の減衰率, クロロフィルα現存量および光合成量子収率を用いた。それぞれの値をもとにアイスアルジーと植物プランクトンの各月の平均日生産量を推定するモデル式を作り, 年生産量を見積もった。氷上に対する海氷下の相対光強度は1年を通して6.5%以下であった。アイスアルジーの単位面積あたりの月平均生産力の最大は12月に34mgCm^<-2>(day)^<-1>であり, 植物プランクトンの生産力の最大は2月に450mgCm^<-2>(day)^<-1>であった。植物プランクトンによる2月の生産量が極めて大きいため, 年間の植物プランクトンの生産量はアイスアルジーによる3.5gCm^<-2>year^<-1>を上回り, 17gCm^<-2>year^<-1>と見積もられた。 Annual primary production of ice algae and phytoplankton under fast ice near Syowa Station (69°00′S, 39°35′E), Antarctica, was estimated. Mean daily production in each month from February 1983 to January 1984 was calculated with a mathematical model based on measured parameters of solar radiation, day length, attenuation coefficients of snow, ice and water, chlorophyll α standing stock, quantum yield for photosynthesis etc. Solar radiation measured at Syowa Station ranged from 0Em^<-2>h^<-1> in June to 13.3Em^<-2>h^<-1> in December. Relative light intensity estimated at the bottom of sea ice during the year ranged from 0 to 6.5% of incident solar radiation, due to attenuation with snow and ice. Maximum daily production of ice algae (34mgCm^<-2>(day)^<-1>) and phytoplankton (450mgCm^<-2>(day)^<-1>) was reached in December and in February, respectively. The estimated annual production of ice algae and phytoplankton was 3.5 and 17gCm^<-2>, respectively. These results indicate that summer phytoplankton production contributed remarkably to the primary production in the coastal ice-covered area near Syowa Station. departmental bulletin paper